European Security and Stability after Kosovo (Czech Journal of International Relations, 2000)
The NATO intervention in Kosovo in the spring of 1999 was the result of the refusal to be inactive and merely watch the abuse of military force and the massacre of the civilian population. The decision about what concrete form it was to take was reflected also by fears that a land operation could have worse effects than air strikes.The positions of the majority of the direct protagonists in the decision-making process were unequivocally in favour of the operation. From the point of view of the impact on the thinking and decisions of dictators, the most important effect of the Allied Farce operation could have been a serious warning given to all politicians who wanted to act in the same way as Milosevic. But in their assessment professional journals point out that fundamental political issues have not been solved, that the stability of the Balkan countries has been further undermined and that innocent people have been subjected to punishment. Amnesty International argued that NATO had not adopted all essential measures to protect the civilian population, as stipulated by Supplementary Protocol I of the Geneva Convention of 1949. At the moment a number of contradictions are linked with decisions on intervention in the name of humanitarian values. The priority of political approaches could well result in the restriction of soldiers’ freedom to take decisions. NATO member states have the greatest potential for carrying out operations of this type, but that also have the lowest potential for making sacrifices.The role of the UN is being questioned and, consequently, the practice of international law is becoming relative. The relative nature of the sovereignty of the state is relative because it threatens only those states which do not possess nuclear weapons and are not permanent members of the UN Security Council. The inequality of states with regard to security, war and peace has become more prominent at the end of the 20th and beginning of the 21st century. The decision-making processes within NATO are, and will continue to be influenced by the position, role and influence of the USA. The conviction, deeply rooted in America, that the US is a model of future society, that the US has a worldwide mission and right to oversee what the others are doing, to judge them and in an extreme situation even to punish them could result in an “erosion” of its present position. In decisions about its security strategy in a period after Kosovo, the US will be able to choose between several alternatives, especially between global unilateralism, advocating the maximum influence and some kind of globalist role of NATO or cooperative security. According to Tony Blair, Kosovo was a triumph of a progressive approach to international relations over the long obsolete traditional concept. Others (including Solana) believe that Kosovo is an exception which neither forms a precedent nor lays down the rules of the game. It is, therefore, nor likely that the conflict between traditions and a new approach towards international relations will be solved in the foreseeable future.There are a number of more or less serious differences and disagreements between states which adopted a negative stance to the NATO intervention in Kosovo, and that is why they can hardly create a compact community advocating a comprehensive strategy against NATO. A return towards a confrontation is, therefore, most unlikely.